Contribution of cashew nut shells as base material in the multi-response optimised automobile brake pad composites in the composition mix - Sadiq Sius Lawal (Maejo International Journal of Energy and Environmental Communication, 2025)
The need to develop automobile brake pad materials from green and environmentally sustainable sources is an increasingly growing research direction. Many researchers have been working towards replacing carcinogenic asbestos with other agro-biomass reinforcements that are readily available, effective, and environmentally friendly. Therefore, Agro-waste such as Cashew Nut Shells has now emerged as a new and inexpensive material that could be used to form parts of brake pads composite matrix that are commercially viable and environmentally acceptable. This paper reports the contribution of Cashew Nut Shells (CNS) as a possible replacement of asbestos as base and reinforcement materials when utilized with other brake pads production ingredients. A total of twenty seven (27) trial composites of particle size 100 μm was generated via Taguchi Design of Experimental method and ANOVA from the optimized Grey Relational Analysis indicated that Cashew Nut Shells (CNS) has the highest significant contribution and effects on the multi-response performance of the developed brake pads composites with percentage contribution (p-value) of 27..558% while that of Granite and Plant Gum binder constituents were 25.892% and 15.479% respectfully.